POLITENESS STRATEGIES IN JAVANESE INDIRECT OFFER USED BY PROSTITUTES IN SURABAYA - Megah, Suswanto Ismadi (Kajian Linguistik dan Sastra, 2008)
Â Politeness becomes important in speech when what is about to be said has the potential to threaten the Hearerâs face. Often in communication it is necessary to say something that would threaten the other personâs face. In other words, Face Threatening Acts (FTA) are committed when the speech behavior is going to po- tentially fail to meet the Hearerâs positive or negative face needs. Doing FTA is a normal speech behavior and is not seen as a problem in itself. The problem arises when the FTA fails to be executed appropriately in order to mitigate potential problems that could result from doing the FTA. Prostitutes are considered as marginalized people, and then women as sub group tend to speak more politely. There are many subordinate groups which have their own set of communication rules, apart from the universal rules. There are different levels of required polite- ness and different ways of being polite, but all people have the need to be appreci- ated and protected, which Brown and Levinson call face needs. This study found interesting features in the way the subjects manipulate and manage their interac- tions in order to get their intended message across employed six positive and seven negative politeness strategies.Â Key words: FTA, Indirectness, Positive and Negative politeness.Â